13-Year-Old Boy Presenting with Bilateral Femur Fractures in the Setting of Severe Vitamin D Deficiency - Marianne Jacob; Marisa Censani (Case Reports in Pediatrics)
Background. Femur fractures in adolescents are rare. Severe vitamin D deficiency has important implications for bone health. We describe the case of a 13-year-old boy with autism spectrum disorder (ASD) who presented with low-impact bilateral femur fractures in the setting of severe vitamin D deficiency. Case Presentation. A 13-year-old boy with ASD presented with bilateral leg pain after an unwitnessed fall. Laboratory investigations revealed severe hypocalcemia (S. calcium 4.9 mg/dL) and severe vitamin D deficiency (25(OH)D < 4 ng/mL). Lower extremity X-rays revealed bilateral distal femoral metaphyseal fractures. Conclusion. This is the youngest known case of bilateral femoral fractures in the setting of severe 25(OH)D deficiency. Children with ASD are especially at risk for 25(OH)D deficiency as many have inadequate nutritional intake. As such, primary care providers may provide a pivotal role in the routine laboratory screening of 25(OH)D in this population.